Triple Peak Day: Work Rhythms of Software Developers in Hybrid Work - Hernandez, Javier; Swain, Vedant Das; Suh, Jina; McDuff, Daniel; Amores, Judith; Ramos, Gonzalo; Rowan, Kael; Houck, Brian; Iqbal, Shamsi; Czerwinski, Mary (IEEE Transactions on Software Engineering, 2024)
The future of work is rapidly changing, with remote and hybrid settings blurring the boundaries between professional and personal life. To understand how work rhythms vary across different work settings, we conducted a month-long study of 65 software developers, collecting anonymized computer activity data as well as daily ratings for perceived stress, productivity, and work setting. In addition to confirming the double-peak pattern of activity at 10:00 am and 2:00 pm observed in prior research, we observed a significant third peak around 9:00 pm. This third peak was associated with higher perceived productivity during remote days but increased stress during onsite and hybrid days, highlighting a nuanced interplay between work demands and work settings. Additionally, we found strong correlations between computer activity, productivity, and stress, including an inverted U-shaped relationship where productivity peaked at around six hours of computer activity before declining on more active days. These findings provide new insights into evolving work rhythms and highlight the impact of different work settings on productivity and stress.